Polypharmacy and pharmacogenomics in high-acuity behavioral health care for autism spectrum disorder: a retrospective study - Sheldon R. Garrison; Sophie A. Schweinert; Matthew W. Boyer; Maharaj Singh; Sreya Vadapalli; Jeffery M. Engelmann; Rachel A. Schwartz; Madeline M. Hartig (Child and Adolescent Psychiatry and Mental Health)
Abstract Background This study evaluated pharmacogenomic (PGx) testing in children and adolescents with autism spectrum disorder (ASD). ASD frequently presents with co-occurring depression and anxiety. This complex phenotype often results in psychotropic medication polypharmacy. Incorporating PGx testing into the medical work-up may reduce polypharmacy and improve quality of life with symptom reduction. Methods A retrospective electronic health record (EHR) review between January 2017 and May 2023. Individuals either received PGx testing or treatment as usual (TAU). The co-primary outcomes were instance of polypharmacy and the Pediatric Quality of Life Enjoyment and Satisfaction Questionnaire (PQ-LES-Q). Secondary outcomes included length of stay, average number of psychotropic medications, readmissions and assessments measuring severity of symptoms or behavioral impact. When at least one daily psychotropic medication was prescribed and reported to have an increased probability of gene–drug interactions, the individual was classified as “incongruent” (PGx-I). Individuals were categorized as “congruent” (PGx-C) if all prescribed psychotropic medications were without potential gene–drug interactions. Polypharmacy was evaluated and compared within the PGx-C and PGx-I subgroups. Results A total of 99 individuals with ASD were analyzed. At the time of admission, 93% of individuals were prescribed at least one psychotropic medication and over half of these individuals were prescribed medications with potential gene–drug interactions. Following PGx testing, there was an overall reduction in prescribed medications with potential gene–drug interactions. No differences were observed between the PGx and TAU groups in polypharmacy, quality of life, or symptom assessments of depression, anxiety, obsessive–compulsive disorder and body-focused repetitive behaviors. Subanalysis comparing congruent (“use as directed”) or incongruent (“use with caution”), as well as exploratory analysis of only CYP2D6 and CYP2C19 gene–drug interactions, were observed to have a similar profile between treatment groups for all primary and secondary outcomes, except for the average number of psychotropic medications prescribed. Conclusions Incorporating PGx testing into the medical workup did not improve outcomes, with all treatment groups achieving similar levels of polypharmacy and quality of life. Analysis of secondary outcomes revealed some differences in medication prescribing when stratifying by congruency; however, no differences were observed between treatment groups for all other secondary outcomes.